Dual-Band Substrate Integrated Waveguide Filters With Perturbed Circular Cavity - Yang, Xian-Long; Zhu, Xiao-Wei; Wang, Xiang (IEEE microwave and wireless components letters, 2022)
In this letter, a novel dual-band substrate integrated waveguide (SIW) filter with the perturbed circular cavity is presented. By introducing three kinds of metallic via perturbations combining different angles of feeding lines, five resonant modes TM 010 , TM 110 (a pair of degenerate modes), and TM 210 (a pair of degenerate modes) are perturbed to design the proposed filter. Thus, a dual-band filter with three transmission poles in the first passband and two transmission poles in the second passband is realized in a single circular cavity. Multiple transmission zeros are generated to increase the out-band performance. Then, a two-cavity dual-band filter is proposed by cascading two identical circular cavities, which shows better out-band suppression and return loss performance. The proposed dual-band filters are designed, fabricated, and measured in a standard printed circuit board (PCB) process at the Q -band and the V -band.